CHANGE IN DEFORMATION PROPERTIES MODELING OF CONCRETE IN PROTECTIVE STRUCTURES OF NUCLEAR REACTOR BY IONIZING RADIATION - E. K. Agakhanov; R. M. Kurachev; A. S. Chepurnenko; S. B. Yazyev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The necessity of studying the effect impact of elementary particles impact on the strength and deformation materials properties used in protective constructions nuclear reactors and reactor technology has been stipulated. A nuclear reactor pressure vessel from prestressed concrete, combining the functions of biological protection is to be considered. The neutron flux problem distribution in the pressure vessel of a nuclear reactor has been solved. The solution is made in axisymmetric with the finite element method using a flat triangular finite element. Computing has been conducted in Matlab package. The comparison with the results has been obtained using the finite difference method, as well as the graphs of changes under the influence of radiation exposure and the elastic modulus of concrete radiation deformations have been constructed. The proposed method allows to simulate changes in the deformation properties of concrete under the influence of neutron irradiation. Results of the study can be used in the calculation of stress-strain state of structures, taking into account indirect heterogeneity caused by the physical fields influence.